Virtual Reality to Promote Tourism in Indonesia - Fauzi, Amir Hasanudin; Gozali, Alfian Akbar (Jurnal Sistem Komputer, 2015)
Abstractâ€” Tourism is an important source of income for many countries, especially in Indonesia. Indonesia is famous for its archipelago and tropic climate islands. Many tourists have visited Indonesia for leisure, business, and other purposes. To attract and increase potential tourists to travel to Indonesia, a promoting activities need to be done. However, these activities can only be done through a conventional flat display of a television, computer, or a smartphone. The information perceived from this kind of display only brings that much. The potential tourist can only â€œseeâ€ the advertisement, without feeling any interest in it. With the help of Virtual Reality Technology, an immersive advertisement about tourism can be created. Using the Oculus Rift DK2, this paper will explain how to integrate the promoting activities of tourism with the Virtual Reality Technology to create an immersive virtual world of Tourism to attract a potential tourist to visit Wonderful Indonesia.Tourism is an important source of income for many countries, especially in Indonesia. Indonesia is famous for its archipelago and tropic climate islands. Many tourists have visited Indonesia for leisure, business, and other purposes. To attract and increase potential tourists to travel to Indonesia, a promoting activities need to be done. However, these activities can only be done through a conventional flat display of a television, computer, or a smartphone. The information perceived from this kind of display only brings that much. The potential tourist can only â€œseeâ€ the advertisement, without feeling any interest in it. With the help of Virtual Reality Technology, an immersive advertisement about tourism can be created. Using the Oculus Rift DK2, this paper will explain how to integrate the promoting activities of tourism with the Virtual Reality Technology to create an immersive virtual world of Tourism to attract a potential tourist to visit Wonderful Indonesia.